Relationship between The Adsorption Capacity of Pesticides by Wood Residues and The Properties of Woods and Pesticides - Rodriguez-Cruz, Sonia; Andrades, Maria S.; Sanchez-Camazano, Maria; Sanchez-Martin, Maria J. (Environmental Science & Technology, 2007)
With the aim to explore the potential use of wood residues in technologies aimed at preventing the pollution of soil and water, we studied the adsorption of four non-ionic pesticides (linuron, alachlor, metalaxyl, and chlorpyrifos) and two ionic pesticides (dicamba and paraquat) with a Kow range of ?4.5 to 4.7 by nine types of wood with lignin content in the 18.2?26.9% range. The Freundlich Kf values were considered as indicators of the adsorption capacity. A statistical study was carried out using simple and multiple correlations to establish the degree to which the different parameters of the woods and of the pesticides were involved in adsorption. In the case of the non-ionic pesticides, positive and negative significant correlations were observed between Kf and the lignin (r = 0.73?0.83, p < 0.05?0.01), and soluble C contents of the woods (r = 0.66?0.84), p < 0.1?0.01). For dicamba, a correlation between Kf and pH (r = ?0.66, p < 0.1) of the woods was found, while for paraquat, this was seen between Kf and the cation exchange capacity (r = 0.71, p < 0.1) of the woods. No significant correlation was observed between Kf and the total C content of the woods. A highly significant correlation between Kf and Kow values (r ≥ 0.93, p < 0.01) was found in the adsorption of the pesticides by the woods (with the exception of paraquat) showing that this parameter is very important in this adsorption process. The determination coefficient of the multiple correlation between Kf and the parameters Kow, soluble C, and lignin contents accounts for nearly 100% of the variability in adsorption for non-ionic pesticides. Based on the results of our study and of those of the literature related to the adsorption of aromatic hydrocarbons, we used the Kow values to define a predictive model of adsorption of hydrophobic organic compounds in general by the woods.
doi: 10.1021/es062616fdoi: 10.1021/es062616fThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: lignin content; pesticide adsorption; wood properties (voyant); wood residues

Relationship between The Adsorption Capacity of Pesticides by Wood Residues and The Properties of Woods and Pesticides - Rodriguez-Cruz, Sonia; Andrades, Maria S; Sanchez-Camazano, Maria; Sanchez-Martin, Maria J (Environmental Science & Technology, 2007)
With the aim to explore the potential use of wood residues in technologies aimed at preventing the pollution of soil and water, we studied the adsorption of four non-ionic pesticides (linuron, alachlor, metalaxyl, and chlorpyrifos) and two ionic pesticides (dicamba and paraquat) with a Kow range of ?4.5 to 4.7 by nine types of wood with lignin content in the 18.2?26.9% range. The Freundlich Kf values were considered as indicators of the adsorption capacity. A statistical study was carried out using simple and multiple correlations to establish the degree to which the different parameters of the woods and of the pesticides were involved in adsorption. In the case of the non-ionic pesticides, positive and negative significant correlations were observed between Kf and the lignin (r = 0.73?0.83, p < 0.05?0.01), and soluble C contents of the woods (r = 0.66?0.84), p < 0.1?0.01). For dicamba, a correlation between Kf and pH (r = ?0.66, p < 0.1) of the woods was found, while for paraquat, this was seen between Kf and the cation exchange capacity (r = 0.71, p < 0.1) of the woods. No significant correlation was observed between Kf and the total C content of the woods. A highly significant correlation between Kf and Kow values (r ≥ 0.93, p < 0.01) was found in the adsorption of the pesticides by the woods (with the exception of paraquat) showing that this parameter is very important in this adsorption process. The determination coefficient of the multiple correlation between Kf and the parameters Kow, soluble C, and lignin contents accounts for nearly 100% of the variability in adsorption for non-ionic pesticides. Based on the results of our study and of those of the literature related to the adsorption of aromatic hydrocarbons, we used the Kow values to define a predictive model of adsorption of hydrophobic organic compounds in general by the woods.
doi: 10.1021/es062616f
Keywords: lignin content; pesticide adsorption; wood properties (voyant); wood residues

Pesticide sorption on soils treated with evergreen oak biomass at different humification stages - Martinez-Iñigo, M J; Almendros, G (Communications in Soil Science and Plant Analysis, 1992)
Abstract The sorption of twelve pesticides (alachlor, atrazine, carbofuran, 2,4?D, 2,4?DB, methyl parathion, metoxuron, monuron, prometryne, propanil, silvex and spergon) was studied on two soil samples with a different carbonate content and treated with evergreen oak (Quercus ilex L. subsp. ballota) biomass at successive humification stages. The direct interaction between the above pesticides and lignocellulosic materials was also assayed independently. After the samples were suspended in 25 ppm pesticide solutions for 12 h, the concentrations in the supernatants were measured by derivatographic UV spectroscopy. The major fixations on the biomass of evergreen oak were found for spergon, prometryne and propanil. Except for atrazine, carbofuran, prometryne and silvex, composting the forest residue for 87 weeks significantly increased pesticide sorption. No correlations were found between the sorption values measured directly in the lignocellulosic materials and those in the soils amended with the latter, indicating the conspicuous influence of organo?mineral interactions in the soil. Calcium carbonate played an important role in pesticide sorption: the lowest pesticide retentions were observed for the samples of the soil with the highest pH, where the addition of organic matter led to the greatest enhancements. The fixation of silvex and carbofuran increased considerably when the organic matter was added to the soil with the lowest pH, whereas in the calcic soil samples the major fixation corresponded to chlorinated phenoxy acids. Possible mechanisms involved in pesticide sorption in the systems studied are discussed.
doi: 10.1080/00103629209368699
Keywords: humification; pesticide adsorption; Quercus ilex L. subsp. ballota; soil pH (PG)